Threatened by Legislative Conservationism? The Case of the Critically Endangered Aeolian Lizard - Gippoliti, Spartaco; Capula, Massimo; Ficetola, Gentile F.; Salvi, Daniele; Andreone, Franco (Frontiers in Ecology and Evolution, 2017)
Species-based conservation legislation must be based on sound scientific data and updated taxonomic knowledge. European Union environmental legislation is among the most advanced in the world, yet there is not a clear and regular mechanism to update species’ lists of Habitats Directive Annexes according the latest available scientific data. Here we review the specific situation of the endemic Aeolian lizard Podarcis raffonei as a case-study of possible species extinction into the Mediterranean biodiversity hotspot as the result of failure to update lists of EU protected species. We suggest to implement a mechanism of periodical revision of the Annexes of the Habitats Directive with particular attention to endemic EU species included in the IUCN Red List as Critically Endangered.